2024
DOI: 10.1097/gox.0000000000005637
|View full text |Cite
|
Sign up to set email alerts
|

Practical Review on the Contemporary Diagnosis and Management of Compartment Syndrome

Amelia L. Davidson,
Mason A. Sutherland,
Robert C. Siska
et al.

Abstract: Summary: Acute compartment syndrome (ACS) is a limb-threatening pathology that necessitates early detection and management. The diagnosis of ACS is often made by physical examination alone; however, supplemental methods such as compartment pressure measurement, infrared spectroscopy, and ultrasound can provide additional information that support decision-making. This practical review aims to incorporate and summarize recent studies to provide evidence-based approaches to compartment syndrome for bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…They obtained values that showed that the average hemoglobin oxygen saturation increased by 15.4% in the compartments of the anatomical segment with fracture injuries as compared to the contralateral limb and healthy subjects. More recent studies [14,27,28] have aimed to objectify the perfusion deficit by using NIR spectroscopy in acute compartment syndrome located at the level of the calf. In all of these patients, invasive determination of the intracompartmental pressure as well as spectroscopic measurement of the contralateral intact leg were performed.…”
Section: Discussionmentioning
confidence: 99%
“…They obtained values that showed that the average hemoglobin oxygen saturation increased by 15.4% in the compartments of the anatomical segment with fracture injuries as compared to the contralateral limb and healthy subjects. More recent studies [14,27,28] have aimed to objectify the perfusion deficit by using NIR spectroscopy in acute compartment syndrome located at the level of the calf. In all of these patients, invasive determination of the intracompartmental pressure as well as spectroscopic measurement of the contralateral intact leg were performed.…”
Section: Discussionmentioning
confidence: 99%
“…Re-examinations at shorter intervals are recommended as they may overlook significant findings. Follow-up visits should include an interview, physical examination with the removal of Sheene fixation, and, if necessary, quantitative ACS diagnostic tests such as Stryker needle, near-infrared spectroscopy (NIRS), ultrasound, and laboratory findings (creatine phosphokinase, creatinine, and urine myoglobin) should be performed [9].…”
Section: Discussionmentioning
confidence: 99%